2021
DOI: 10.1007/s00415-021-10836-8
|View full text |Cite
|
Sign up to set email alerts
|

Early and unrestricted access to high-efficacy disease-modifying therapies: a consensus to optimize benefits for people living with multiple sclerosis

Abstract: Early intervention with high-efficacy disease-modifying therapy (HE DMT) may be the best strategy to delay irreversible neurological damage and progression of multiple sclerosis (MS). In European healthcare systems, however, patient access to HE DMTs in MS is often restricted to later stages of the disease due to restrictions in reimbursement despite broader regulatory labels. Although not every patient should be treated with HE DMTs at the initial stages of the disease, early and unrestricted access to HE DMT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
57
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(58 citation statements)
references
References 37 publications
(53 reference statements)
1
57
0
Order By: Relevance
“…Disease‐modifying therapies (DMTs) and immune reconstitution therapies (IRTs) are used to treat patients with MS (pwMS) to decrease relapses, or new MRI lesions in the brain and spine, and to slow disability progression. 1 The coronavirus disease 2019 (COVID‐19) pandemic is concerning in pwMS due to possible increased susceptibility to COVID‐19, considering many potential interactions with the immune system, neurological complications associated with SARS‐CoV‐2 infection and the immunosuppressive effects of DMTs. 2 , 3 These complications include an increased risk of death due to COVID‐19 in pwMS who have significant neurological disability.…”
Section: Introductionmentioning
confidence: 99%
“…Disease‐modifying therapies (DMTs) and immune reconstitution therapies (IRTs) are used to treat patients with MS (pwMS) to decrease relapses, or new MRI lesions in the brain and spine, and to slow disability progression. 1 The coronavirus disease 2019 (COVID‐19) pandemic is concerning in pwMS due to possible increased susceptibility to COVID‐19, considering many potential interactions with the immune system, neurological complications associated with SARS‐CoV‐2 infection and the immunosuppressive effects of DMTs. 2 , 3 These complications include an increased risk of death due to COVID‐19 in pwMS who have significant neurological disability.…”
Section: Introductionmentioning
confidence: 99%
“…A recent article by Filippi M et al mentioned that use of oral and self-administered DMTs could lead to reduction in costs for health care systems mainly in terms of hospital occupation, and in the risk of infection; additionally, it could attenuate the di culties in access to care caused by the COVID-19 pandemic. 19 Per the ofatumumab label, the rst injection of ofatumumab should be performed under the guidance of an appropriately trained HCP. Thereafter, ofatumumab is intended for patient self-administration.…”
Section: Discussionmentioning
confidence: 99%
“…13,20 In this survey, we found that 40% of the treating physicians would favour the use of ofatumumab for treatment-naïve patients; 87% prefer to use ofatumumab as rst escalation therapy and 68% prefer to use it as second escalation therapy. A recently published article determined that an early and unrestricted access to high-e cacy (HE) DMTs including ofatumumab for people living with MS in Europe, showed a positive bene t-risk pro le and improved outcomes indicating that the early use is the best strategy to delay the progression of MS. 19 HEDMTs (including alemtuzumab, ngolimod, ocrelizumab, and ofatumumab) have demonstrated improved e cacy versus interferons or teri unomide in reducing relapse rates, MRI lesions, brain volume loss, and/or delaying disease progression across several clinical programs. 13,[21][22][23] In the Phase 3 ASCLEPIOS trials, 9 ofatumumab was administered in a pre-lled syringe; however, ofatumumab is approved in Europe 12 as a pre-lled syringe and an autoinjector pen.…”
Section: Discussionmentioning
confidence: 99%
“…This would be particularly beneficial in pandemic times, since “high-efficacy” but higher risk IMDs interfere with immune responses to vaccines [ 32 ]. Conversely, treatment with “high efficacy” IMDs (HE IMDs) [ 33 , 34 , 35 , 36 ], with a higher risk profile, might be better suited for patients with positive neuroinflammation predictive biomarkers.…”
Section: Two Logical Candidates For Molecular Biomarkers Based On The...mentioning
confidence: 99%